Immunological Assessment of Pediatric Multisystem Inflammatory Syndrome Related to Coronavirus Disease 2019. (12th November 2020) - Grazioli, Serge; Tavaglione, Fedora; Torriani, Giulia; Wagner, Noemie; Rohr, Marie; L'Huillier, Arnaud G; Leclercq, Charlotte; Perrin, Anne; Bordessoule, Alice; Beghetti, Maurice; Schmid, Jana Pachlopnik; Vavassori, Stefano; et al.
Abstract: Background: Recently, cases of multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus disease 2019 (COVID-19) have been reported worldwide. Negative polymerase chain reaction (RT-PCR) testing associated with positive serology in most of the cases suggests a postinfectious syndrome. Because the pathophysiology of this syndrome is still poorly understood, extensive virological and immunological investigations are needed. Methods: We report a series of 4 pediatric patients admitted to Geneva University Hospitals with persistent fever and laboratory evidence of inflammation meeting the published definition of MIS-C related to COVID-19, to whom an extensive virological and immunological workup was performed. Results: RT-PCRs on multiple anatomical compartments were negative, whereas anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin A (IgA) and immunoglobulin G (IgG) were strongly positive by enzyme-linked immunosorbent assay and immunofluorescence. Both pseudoneutralization and full virus neutralization assays showed the presence of neutralizing antibodies in all children, confirming a recent infection with SARS-CoV-2. The analyses of cytokine profiles revealed an elevation in all cytokines, as reported in adults with severe COVID-19. Although differing in clinical presentation, some features of MIS-C show phenotypic overlap with hemophagocytic lymphohistiocytosis (HLH). In contrast to patients with primary HLH, our patients showed normal perforin expression and natural killer (NK) cell degranulation. The levels of soluble interleukin (IL)-2 receptor (sIL-2R) correlated with the severity of disease, reflecting recent T-cell activation. Conclusion: Our findings suggest that MIS-C related to COVID-19 is caused by a postinfectious inflammatory syndrome associated with an elevation in all cytokines, and markers of recent T-cell activation (sIL-2R) occurring despite a strong and specific humoral response to SARS-CoV-2. Further functional and genetic analyses are essential to better understand the mechanisms of host–pathogen interactions. Abstract : The pathophysiology of multisystem inflammatory syndrome in children related to coronavirus disease 2019 is unclear. We show that there is a postinfectious inflammatory syndrome with elevation in all cytokines despite confirmation of a strong and specific humoral response to SARS-CoV-2. The expressions of perforin and NK cell degranulations were normal despite overlapping phenotype with hemophagocytic lymphohistiocytosis.